Prognostic value of the NEWS + Lactate score in patients with decompensated heart failure in the emergency department - Mustafa Can Guzelce; Nese Colak; Gucluhan Ucar; Ertug Orhan (ESC Heart Failure, 2023)
Abstract Aims The National Early Warning Score (NEWS) is a scoring system that predicts increased mortality and morbidity in critical diseases. The National Early Warning Score + Lactate (NEWS + L) score was created by adding lactate values to this scoring system. In our study, we aimed to determine the value of the NEWS + L score in predicting clinical deterioration in patients presenting with acute decompensated heart failure (chronic heart failure). Methods and results In this observational, cross‐sectional study, patients with decompensated heart failure who were admitted to the emergency department between 1 October 2020 and 31 December 2020 were included. Patients were divided into two groups: those with and without poor prognostic outcomes. The main outcomes were in‐hospital mortality, discharge after treatment in the emergency department, admission to the ward, and admission to the intensive care unit. We analysed a total of 141 applications from 130 patients. The mean age was 72.6 ± 11.8 years, and 50.8% were female. Poor prognostic outcomes were observed in 92 (65%) patients. There was no difference between the patients with and without poor prognostic outcomes in terms of mean age, gender, and comorbidities, except for atrial fibrillation. There was a statistically significant difference between the patients without and with poor prognosis outcomes in terms of NEWS {3 [interquartile range (IQR): 0–5] and 6 [IQR: 3–8]} and NEWS + L scores [4.7 (IQR: 2.3–7.2) and 8.0 (IQR: 5.2–10.4)] (P < 0.001). The area under the curve values for predicting poor prognosis were calculated as 0.719 for NEWS, 0.734 for NEWS + L, and 0.601 for lactate values. The rate of poor prognostic outcomes was higher (79%) in patients with moderate and high NEWS scores. Patients with Q1 NEWS + L scores had a lower rate of poor prognostic outcomes, while patients with Q2, Q3, and Q4 scores of NEWS + L had a higher rate of poor prognostic outcomes. Conclusions The NEWS score and the addition of the lactate value to this score, the NEWS + L score, were higher in patients with poor prognostic outcomes who presented with decompensated heart failure in our emergency department. NEWS + L slightly outperformed the NEWS score in predicting prognosis. The NEWS + L score shows promise as a prognostic indicator for patients with decompensated heart failure presenting to the emergency department.